Tibetan manuscripts and early printed books - Kapstein, Matthew T. 1949- (Cornell University Press, 2024)
"Brings together recent research on the Tibetan book. Volume I includes the manufacture of paper and ink, format and layout, scripts and scribal conventions, illumination and decoration, woodblock printing, book storage, and the use of digital technologies for documentation. Volume II surveys manuscript collections comprising Buddhist scriptural canons, official and administrative documents, works on technical subjects, and Tibetan books from China and Mongolia"--
Keywords: Geschichte; Handschriftenkunde; Buchdruck; Paläographie; Buch; Papierherstellung; Tibetische Schrift; Tibet; Books / Tibet Region / History; Manuscripts / Tibet Region / History; Printing / Tibet Region / History